Analisis Faktor-Faktor Yang Mempengaruhi Persepsi Pelaku Usaha Mikro Kecil Menengah (UMKM) Tentang Pentingnya Pelaporan Keuangan Berdasarkan SAK ETAP - Dia Maya Sari; Siti Asiam (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
MSMEs play an important role in the Indonesian economy. This research aims to analyze the influence of education level, business size, length of business, and participation in the SAK EMKM coaching program on the perception of the importance of financial reporting based on SAK EMKM. The data used in this research are primary data and secondary data. Primary data is in the form of answers from respondents using a questionnaire, while secondary data is obtained from information on MSME data from the Regional Technical Implementation Unit of the Bandar Laksamana District Cooperative. The population in this study were all MSMEs in Bandar Laksamana District with a total of 175 units. The sample used in this research was 64 MSMEs in Bandar Laksamana District using a simple random sampling method. The research results show that educational level, length of business, and business size do not influence to the perceptions of importance of financial reporting based on SAK EMKM, only the variable participation in a coaching program influences to the perceptions of the importance of financial reporting based on SAK EMKM.